Management of congenital flexural tendon contractures with stretching in calves - SAĞLAM, K (Journal of the Hellenic Veterinary Medical Society, 2021)
It has been reported that mild to moderate congenital flexural limb contractures of the calves can be treated with stretching. This study was carried out on eleven calves with mild to moderate flexural foot - tendon contractures (three mild and eight moderate cases). The mild cases were treated successfully with only splints or wooden hoof block/PVC application adhered to the ground under the sole of the hoof with acrylic adhesive. The moderate cases, however,were treated successfully with the combined application in which a splint was placed on an entire limb to correct it and then a wooden hoof block/PVC was adhered to the ground under the sole of the hoof with an acrylic adhesive.